CURRENT STATUS OF CANINE BRUCELLOSIS IN INDIA - JASROTIA, NANCY; GULAGI, NAGARAJ; PATRA, MANAS KUMAR; KUJUR, ANJU (The Indian Journal of Animal Reproduction, 2021)
Canine brucellosis is a bacterial disease caused by Brucella canis which is the most common cause of reproductive failure in dogs. Incidence of the disease is higher in stray dogs than in pets. Though brucellosis was reported to have existed in India since 1879, the methodical study was taken up as late as 1943, in animals and man in Madras presidency. However, contagious abortion in livestock associated with brucellosis was first investigated in India by the Imperial Veterinary Research Institute, Mukteshwar in 1918. Since then the disease has been reported almost everywhere in India. Data on the prevalence of canine brucellosis in India is scarce or rather unreported, and the public health significance is not much known. Routine sero-surveillance of canines should also be done so that proper control measures can be taken.